Determinasi Kepuasan Pelanggan Melalui Kualitas Produk dan Kualitas Pelayanan - Suhroji Adha; Etty Nurkhayati; Irawan Irawan; Nani Yunarsih; Djaka Adiwinata (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
This study was conducted to determine the effect of Product Quality and Service Quality on Customer Satisfaction. This type of research is explanatory, with data collection techniques through questionnaires. The sampling technique uses a saturated sample technique, the sample is 80 people who are Outlet employees. The analysis method used in this study is Quantitative Data Analysis. The results of the hypothesis test show that Product Quality has a positive and significant effect on Customer Satisfaction, Service Quality also has a positive and significant effect on Customer Satisfaction. The conclusion of this study is that Product Quality and Service Quality have a positive and significant effect on Customer Satisfaction both partially and simultaneously.